ANALISIS PEMANFAATAN LIMBAH BATU BARA BOTTOM ASH TERHADAP STABILITAS DAN KEPADATAN ASPAL BETON AC-WC - Farlin Rosyad; Mega Putri Pertiwi (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2024)
Roads are the most important infrastructure in the land transportation system in Indonesia. Guaranteeing a good pavement structure will ensure the continuity of a good transportation system as well. In Indonesia, there is a lot of waste from factories that has not been utilized optimally. The large amount of waste will cause problems in its disposal because apart from the large costs that must be incurred in building disposal facilities, this waste can also pollute the environment. Coal ash becomes waste, so using it as a filler in the AC-WC mixture is one solution to reduce the amount of coal waste itself. In this research, coal waste in the form of bottom ash will be used which will be used as a filler for the stability and density of asphalt concrete (AC-WC). The objectives of this research are as follows: To determine the effect of the bottom ash mixture as a filler on the characteristics of the resulting asphalt concrete marshall. And knowing how much optimization the use of Coal Waste has on the stability of the AC-WC Asphalt Concrete mixture. Based on the results and discussion in the previous chapter, it can be concluded that the effect of bottom ash coal ash substitution on the stability and density values of AC-WC asphalt concrete can be concluded as follows:Based on the results of testing the marshal parameters in terms of the substitution of bottom ash coal ash, it can be concluded that the influence of the stability value on the optimum bottom ash coal ash is at a percentage of 4% in zone 0 with a value of 1,499kg and meets the 2018 Bina Marga specifications Revision 2. Then , the influence of the optimum density value (Bulk Density Standard) is located in zone 2 at a percentage of 4% with a value of 2,352kg. and Based on the results of Marshall parameter testing in terms of variations in bottom ash coal ash substitution, it can be concluded that the use of a mixture of bottom ash coal ash content for asphalt stability and density (AC-WC) lies in a mixture of 4%.